153 Kinerja, Budaya Organisasi dan Gaya Kepemimpinan: Studi pada SMA Swasta DKI Jakarta - Lumban Gaol, Mangiring; Riady, Hanes (Jurnal Ilmu Manajemen, 2012)
This study aims to determine the type of organizational culture and leadership style of principals who practiced in groups of high-performing schools and groups of low-performing schools, especially private schools in Jakarta region. Organizational culture is a philosophy, and pointed out four characteristics the organizational culture, among others: clan, adhocracy, hierarchy, and market, which binds members of the organization as a whole in order to achieve both individual and organizational goals. Furthermore, leadership style is a pattern of behavior designed to integrate individual interests with the organizational ones, among others: autocratic style, pseudo-democratic, laissez-faire, and democratic leadership style. This study used descriptive analysis with nonparametric statistical Chi-Square (?2). The samples of data were taken using an instrument of questionnaires on 50 school principals/vice principal, using judgmental-convinience sampling technique. The analysis result showed that there were significant differences in organizational cultures that practiced at the group of high-performing schools with the group of low-performing schools. This study also found that there are no significant differences in leadership styles practiced in the groups of high-performance and low-performing schools.